Physical and Electrochemical Properties of Soluble 3,4-Ethylenedioxythiophene (EDOT)-Based Copolymers Synthesized via Direct (Hetero)Arylation Polymerization - Guo, Qiang; Zhang, Jincheng; Li, Xiaoyu; Gong, Heqi; Wu, Shuanghong; Li, Jie (Frontiers in Chemistry, 2021)
Over the past decades, π-conjugated polymers (CPs) have drawn more and more attention and been essential materials for applications in various organic electronic devices. Thereinto, conjugated polymers based on 3,4-ethylenedioxythiophene (EDOT) backbone are among the high-performance materials. In order to investigate the structure-property relationships of EDOT-based polymers and further improve their electrochemical properties, a series of organic solvent-soluble EDOT-based alternative copolymers consisting of electron-rich fragments (fluorene P1, carbazole P2 and 3,4-alkoxythiophene P3) or electron-deficient moieties (benzotriazole P4 and thieno[3,4-c]pyrrole-4,6-dione P5) were synthesized via DHAP in moderate to excellent yields (60-98%) with medium to high molecular weights (Mn = 3100-94000 Da). Owing to their various electronic and structural properties, different absorption spectra (λmax = 476, 380, 558, 563 and 603 nm) as well as different speciﬁc capacitances of 70, 68, 75, 51 and 25 F/g with 19%, 10%, 21%, 26% and 69% of capacity retentions after 1000 cycles were observed for P1-P5, respectively. After carefully study through multiple experimental measurements and theoretical calculation, appropriate electronic characteristics, small molecular conformation differences between different oxidative states and well-ordered molecular stacking could improve the electrochemical performance of CPs.